2022: Unpredictability as a constant - Morales-Camacho, María Fernanda (2022)
Last January 18th, 2021 the journal The Economist published a short article titled "The new normal is already here. Get used to it." The article started with an interesting phrase: "The era of predictable unpredictability is not going away". This sentence seems like a paradox and is not new per se, it is relevant since we are living in a world that, after two years of the beginning of the pandemic, it faces quick transformations.